Dermocystidiosis induced by the parasite Dermocystidium sp. in the Paracheirodon axelrodi - Plaul, Silvia Elena (2018)
The Rio Negro floodplain (tributary of the Amazon River) is a natural habitat of the cardinal tetra Paracheirodon axelrodi. In home aquaria, this species has high vulnerability to superficial infetions and is affected by the protist Dermocystidium. Protist cysts were located in the dermis causing lesions reaching in the epidermis. We observed that a few weeks after the introduction of new wild ornamental fish (mostly Hemigrammus sp. or Hyphessobrycon sp.) into established home aquaria, the cardinal tetra fish became infected, suggesting that the new fish could have acted as carriers.